Giant diffuse neurofibroma of the chest wall involving the sternum: Challenging chest wall reconstruction. (May 2021) - Mahajan, Sachin; Jaswal, Vivek; Bansal, Vidur; Sekar, Aravind; Kumar, Vikas
Diffuse neurofibroma is a rare form of neurofibroma, usually reported in the head and neck. To our knowledge, diffuse neurofibroma of the anterior chest wall has not been reported previously. Even rarer is involvement of the sternum in neurofibroma. We report a case of a 30-year-old lady who presented with a rapidly growing, painless giant exophytic mass involving almost the entire anterior chest wall. The tumor mass was infiltrating the sternum. Excision of the tumor left a large full-thickness thoracic defect that was covered using polypropylene mesh beneath a pedicled omental flap with a split skin graft over it.